Policy in the Soviet bloc on aid to developing countries - Vasilev, Vasil Atanasov (Paris : Development Centre of the Organization for Economic Co-operation and Development, 1969)
This book is a report of investigation into the scale and forms of aid supplied by the Soviet bloc, and more specifically by Russia. It also contains detailed analysis of the USSR's dealings both with the East European bloc and with the chief countries of the Third World, backed by valuable documentary material.
Bibliography: p. 103-106.
usc 16/05/18
Loans
Keywords: Economic assistance, Soviet; Economic assistance, Russian; Developing countries; International economic relations; Europe, Eastern; Communist countries